Biophotonics - A powerful tool for non-invasive and labelfree cell- and tissue screening - Popp, Jürgen (2017 Conference on Lasers and Electro-Optics, CLEO 2017 - Proceedings, 2017)
In this presentation, we will highlight our recent advances in translating biophotonic approaches with special focus on linear and non-linear Raman spectroscopy towards routine clinical applications with focus on infectious diseases and cancer.
CRIS-Team Scopus Importer:2023-04-20